How do Dutch GPs address work-related problems? A focus group study. (2nd July 2016) - de Kock, Cornelis A.; Lucassen, Peter L. B. J.; Spinnewijn, Laura; Knottnerus, J. André; Buijs, Peter C.; Steenbeek, Romy; Lagro-Janssen, Antoine L. M.
Abstract: Background: In the Netherlands, there is a lack of knowledge about general practitioners' (GPs) perception of their role regarding patients' occupation and work related problems (WRP). As work and health are closely related, and patients expect help from their GPs in this area, a better understanding is needed of GPs' motivation to address WRP. Objectives: To explore GPs' opinions on their role in the area of work and health. Methods: This is a qualitative study using three focus groups with Dutch GPs from the catchment area of a hospital in the Southeast of the Netherlands. The group was heterogeneous in characteristics such as sex, age, and practice setting. Three focus groups were convened with 18 GPs. The moderator used an interview guide. Two researchers analysed verbatim transcripts using constant comparative analysis. Results: We distinguished three items: (a) work context in a GP's integrated consultation style; (b) counselling about sick leave; (c) cooperation with occupational physicians (OPs). The participants are willing to address the topic and counsel about sick leave. They consider WRP in patients with medically unexplained symptoms (MUS) challenging. They tend to advise these patients to continue working as they think this will ultimately benefit them. Conclusion: The participating GPs seemed well aware of the relation between work and health but need more knowledge, communication skills and better cooperation with occupational physicians to manage work-related problems.